Infrared Spectroscopy Principles, Advances, and Applications - El-Azazy, Marwa (IntechOpen, 2019)
Delving into Infrared Spectroscopy: Principles, Advances and Applications, and with basic knowledge of IR spectroscopy, will provide the reader with a synopsis of fundamentals and groundbreaking advances in the field. Readers will see a variety of MIR applications and difficulties encountered, especially in an industrial environment. Competency in FT-IR spectroscopy in biomedical research and early-stage diagnosis of obesity is shown. Challenges associated with VIS-NIR applications are shown through application of the technique in assessing quality parameters of fruits. Moreover, IR spectroscopic studies of radiation-stimulated processes, and the influence of using IR in developing an ideal catalyst and hence an efficient catalysis process, are discussed. The impact of coupling multivariate data analysis techniques to IR is shown in almost every chapter.